Advancements and Future Prospects of Electric Vehicle Technologies: A Comprehensive Review. (1st July 2022) - Hossain, M. S.; Kumar, Laveet; El Haj Assad, Mamdouh; Alayi, Reza
Abstract : Greenhouse gas (GHG) emissions are one of the major problems that the world is facing nowadays. The transportation sector, where vehicles run on oil, contributes a large amount of GHG. The development of electric vehicles to meet the allowed GHG limits has recently been the main focus of research worldwide. Research in electric vehicles (EVs) has observed a tremendous upsurge in recent years. However, reviews that analyze and present the demand and development of EVs comprehensively are still inadequate, and this integrative review is an effort to fill that gap. This study has revealed many thought-provoking understandings related to specific developments, specifically global demand and growth of EVs along with electricity and battery demand, current technological developments in EVs, energy storage technologies, and charging strategies. It also details the next generation of EVs and their technological advancements, such as wireless power transfer. The development of a smart city concept by EV implementation added a new aspect to this review. The summary would be advantageous to both scholars and policymakers, as there has been a lack of integrative reviews that assessed EVs' global demand and development simultaneously and collectively. This review concludes the intuitions for investors and policymakers to envisage electric mobility.